2003
DOI: 10.1136/gut.52.10.1442
|View full text |Cite
|
Sign up to set email alerts
|

Short chain fatty acids stimulate epithelial mucin 2 expression through differential effects on prostaglandin E1 and E2 production by intestinal myofibroblasts

Abstract: Background: The mucus layer protects the gastrointestinal mucosa from mechanical, chemical, and microbial challenge. Mucin 2 (MUC-2) is the most prominent mucin secreted by intestinal epithelial cells. There is accumulating evidence that subepithelial myofibroblasts regulate intestinal epithelial cell function and are an important source of prostaglandins (PG). PG enhance mucin secretion and are key players in mucoprotection. The role of bacterial fermentation products in these processes deserves further atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
256
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(266 citation statements)
references
References 43 publications
9
256
0
1
Order By: Relevance
“…Beneficial bacteria increase the concentration of short-chain fatty acids (SCFAs), such as acetic, propionic and butyric acids. These SCFAs have numerous important roles in the colon, including maintaining the acidity of the intestinal environment, stimulating the proliferation of epithelial cells and intestinal motility, enhancing the secretion of mucin by the epithelium and acting as metabolites for energy metabolism in epithelial cells (23). In the present study, intestinal peristalsis was improved earlier in group B than group A.…”
Section: Discussionsupporting
confidence: 56%
“…Beneficial bacteria increase the concentration of short-chain fatty acids (SCFAs), such as acetic, propionic and butyric acids. These SCFAs have numerous important roles in the colon, including maintaining the acidity of the intestinal environment, stimulating the proliferation of epithelial cells and intestinal motility, enhancing the secretion of mucin by the epithelium and acting as metabolites for energy metabolism in epithelial cells (23). In the present study, intestinal peristalsis was improved earlier in group B than group A.…”
Section: Discussionsupporting
confidence: 56%
“…In poultry, butyrate enhances nonspecific intestinal defense mechanisms against pathogens that can affect performance, such as Clostridium perfringens, by stimulating the mucin glycoprotein expression in intestinal epithelial cells (57)(58)(59). Butyrate is a major energy source for the colonocytes and exerts anti-inflammatory activities by several mechanisms (60).…”
Section: Discussionmentioning
confidence: 99%
“…One of such effects is to modulate the production of PGE2-a key mediator in the initiation and resolution of inflammation and in the transition from innate to acquired immune responses (Fig. 3) [82,181]. Cox et al [82] showed that SCFAs can induce human monocyte release of PGE2.…”
Section: Scfas Induction Of Tregs By Prostaglandin E2 (Pge2)mentioning
confidence: 99%